Transparent PDMS Bioreactors for the Fabrication and Analysis of Multi-Layer Pre-vascularized Hydrogels Under Continuous Perfusion - Liu, Juan; Zheng, Huaiyuan; Dai, Xinyi; Poh, Patrina S. P.; Machens, Hans-Günther; Schilling, Arndt F. (Frontiers in Bioengineering and Biotechnology, 2020)
Tissue engineering in combination with stem cell technology has the potential to revolutionize human healthcare. It aims at the generation of artificial tissues that can mimic the original with complex functions for medical applications. However, even the best current designs are limited in size, if the transport of nutrients and oxygen to the cells and the removal of cellular metabolites waste is mainly dependent on passive diffusion. Incorporation of functional biomimetic vasculature within tissue engineered constructs can overcome this shortcoming. Here, we developed a novel strategy using 3D printing and injection molding technology to customize multilayer hydrogel constructs with vascularized structures in transparent Polydimethysiloxane (PDMS) bioreactors. These bioreactors can be directly connected to continuous perfusion systems without complicated construct assembling. Mimicking natural layer-structures of vascular walls, multilayer vessel constructs were fabricated with cell-laden fibrin and collagen gels respectively. The multilayer design allows functional organization of multiple cell types , i.e. mesenchymal stem cells (MSCs) in outer layer, human umbilical vein endothelial cells (HUVECs) the inner layer and smooth muscle cells (SMCs) in between MSCs and HUVECs layers. Multiplex layers with different cell types showed clear boundaries and growth along the hydrogel layers. This work demonstrates a rapid, cost-effective, and practical method to fabricate customized 3D-multilayer vascular models. It allows precise design of parameters like length, thickness, diameter of lumens and the whole vessel constructs resembling the natural tissue in detail without the need of sophisticated skills or equipment. The ready-to-use bioreactor with hydrogel constructs could be used for biomedical applications including pre-vascularization for transplantable engineered tissue or studies of vascular biology.